Barriers and strategies to improve vaccine adverse events reporting: views from health workers and managers in Northern Ghana - Daniel Weibel; Abraham Oduro; Miriam Sturkenboom; Nana Akosua Ansah; Samuel Tomilola Oladokun; Enyonam Duah; Patrick Ansah; Samuel Tamti Chatio; Marieke Hollestelle (BMJ Public Health, 2025)
Background The increasing incidence of novel vaccine-preventable diseases, such as COVID-19, has led to an increase in the development of vaccines globally. Vaccine hesitancy has risen due to fears of vaccines causing harm. African health systems have generally relied on spontaneous reporting of adverse events following immunisation (AEFIs) to monitor vaccine safety.Objectives This study explored the views of healthcare professionals and managers regarding barriers and strategies to improve AEFI reporting in northern Ghana.Methods This study used a qualitative research design where in-depth interviews were conducted with health professionals and managers in five administrative regions in northern Ghana between March and August 2021. The purposive sampling method was used to select districts and participants. The interviews were audio recorded, transcribed, and coded into themes using QSR NVivo V.12 software before thematic content analysis.Results The study found that lack of feedback is the main regulatory-level factor affecting reporting adverse events. Health system-level factors, such as limited knowledge of reporting AEFIs, a lack of training, difficulties in using electronic application software to complete AEFI forms, and fear of punishment, significantly affect AEFI reporting. At the patient/community level, the main factors affecting AEFI reporting are the distance to health facilities and transportation costs. However, participants suggested continuous AEFI education, sensitisation of health workers and patients, timely feedback, and effective stakeholder collaboration among front-line health workers, health managers, and the national pharmacovigilance authority could improve AEFI reporting in Ghana.Conclusions Reporting of AEFIs contributes to improving vaccine safety, surveillance systems and prompt case management. However, the study identified multiple key factors at the regulatory, health system, and patient levels affecting AEFI reporting. Thus, improvements in line with these suggestions, including effective stakeholder engagement, are necessary to increase AEFI reporting.